Knowledge, attitude, and practice of healthcare workers on early gastrointestinal cancer in China - Zhang, Hui; Zhao, Changdong; Song, Chengwen; Wu, Youshan; Wei, Dongying; Li, Xiuqing (Frontiers in Public Health, 2023)
Objective: Gastrointestinal cancer is leading cause of cancer-related death in China, and its early screening is largely recommended by healthcare workers. This study investigated the knowledge, attitudes, and practice (KAP) of healthcare workers on early gastrointestinal cancer (EGC). Methods: This cross-sectional study was conducted on healthcare workers who were volunteered to participate from 30 hospitals in China between September and December, 2022. A self-administered questionnaire included 37 questions was developed. Results: A total of 545 completed questionnaires were finally obtained. Healthcare workers had moderate knowledge level [9.22±1.80 (65.8812.89%), total score: 14], positive attitude [21.84±2.67 (91.0111.14%), total score: 24], and excellent practice level [19.07±4.43 (79.4718.44%), total score: 24] on EGC. Pearson’s correlation analysis suggested that knowledge score was positively correlated with attitude (r=0.264, P<0.001) and practice score (r=0.140, P=0.001), and higher attitude score was significantly correlated with higher practice score (r=0.380, P<0.001), which were supported and reinforced by structural equation modeling. In addition, subgroup analysis showed that knowledge scores might be influenced by sex, age, education, type of hospital, type of occupation, professional title and years of working (all P<0.05); attitude scores might be influenced by years of working (P<0.05); and practice scores were statistically distinct among groups of different sex, department, and years of working (all P<0.05). Conclusion: Healthcare workers have moderate knowledge level, positive attitude, and excellent practice level on EGC. Good knowledge and positive attitude might be correlated with excellent practice. KAP level might be influenced by sociodemographic characteristics.